The Relationship of Emotional intelligence with Women's Post-abortion Grief and Bereavement - Nahid Golmakani; Maryam Ahmadi; Negar Asgharipour; Habibollah Esmaeli (Mashhad University of Medical Sciences, 2018)
Background & aim: Emotional intelligence (EQ) is one of the factors influencing post-abortion grief and bereavement. This study aimed to determine the relationship between the level of EQ and post-abortion grief and bereavement in women referred to the hospitals affiliated to Mashhad University of Medical Sciences. Methods: This correlational study was conducted on 60 women with spontaneous abortion admitted in Department of Obstetrics and Gynecology of Imam Reza, Ghaem, and Omolbanin hospitals, Mashhad, Iran in 2016. The subjects were selected through convenience sampling and data were collected using a self-structured questionnaire, Bar-On model of socio-emotional intelligence, grief intensity scale, and perinatal Grief and Bereavement Scale. Data analysis was performed using descriptive statistics, simple linear regression, and Pearson correlation coefficient in SPSS software version 11.5. Results: The subjects' mean age was 28.6±5.7 years old and 73.3% (n=44) of them were housewives. The mean scores of post-abortion grief, bereavement, and EQ were 126.5±26.7, 42.7±9.4, and 188.4±17.9, respectively. According to the results of linear regression analysis, the EQ adversely and significantly predicts the post-abortion grief (P=0.001, β=-43.22) and bereavement (P